Collaboration of Greek-Catholic church with Ukrainians in America in 20-30 of XX century - Pylypiv, Ihor (Skhid, 2013)
This article examines the activity of Greek-Catholic church in organization of collaboration with Ukrainian Greek-Catholic communities on the American continent. Using concrete examples, the author illustrates a systematic activity of Lviv Greek-catholic commune in supporting emigrants-Ukrainians to theUnited States, which was shown in spiritual, organizational, clerical, and moral support.